Larvicidal Effects Of Pongamiaglabra and Syzygiumaromaticum On Aedes Aegypti Mosquito Larvae: Life Sciences-Entomology for Better Antimalarial Activity - Ananya Bar; J. Andrew; Akshay Botle; Manojsingh (International Journal of Life Science and Pharma Research, 2022)
Mosquitoes are considered as the most nuisance causing vectors as they are responsible for a widespread of diseases. Malaria-borne mosquitoes are responsible of killing two to three million people and infect an estimated two hundred million or more annually. A host of other mosquito-borne diseases including filariasis, yellow fever, dengue, and encephalitis kill and debilitate hundreds of millions more. The present study investigates the bio efficacy of two commercially available plant oils from Pongamia glabra (Karanja) and Syzygium aromaticum (Clove). These two plant oils were tested against Aedes aegypti (Dengue fever mosquito) to determine their lethal concentration doses (LC50). A larval toxicity assay was performed where a stock solution of 10% was prepared for both the oils at a concentration range of 100 to 900 ppm and 90 to 1300 ppm was set for Pongamia glabra and Syzygium aromaticum respectively. A batch of each 10 IVth instar larvae was subjected to the assay with test, combination and a control set for a period of 24 and 48 hrs. LC50 of two oils were determined while the combination of two oils showed a synergistic effect. The effect of P. glabra and S. aromaticum on the anterior and posterior regions of the midgut region of A. aegypti larvae were found damage to epithelial cells, basement membrane, peritrophic membrane, fat body cells and nuclei were observed. The results of the study showed that the synergistic method of using common eco-safe combination of plant oils were effective to handle and monitor A. aegypti larva. Pongamia glabra and Syzygium aromaticum are among the successful mosquito control agents.